2008
DOI: 10.1080/14017430701747108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vein graft intimal hyperplasia by periadventitial application of hyaluronic acid–carboxymethyl cellulose: An experimental study

Abstract: Periadventitial placement of HA/CMC as an absorbable membrane inhibits intimal hyperplasia of vein bypass grafts in a rabbit model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…To investigate whether external support would reduce intimal hyperplasia at the site of venous graft anastamosis, rabbits undergoing bypass grafting of the right jugular vein to the right common carotid artery was performed in the presence or absence of wrapping the anastamosis with Seprafilm [67]. Evaluation at 1 month demonstrated that use of Seprafilm reduced both neointimal and medial thickening.…”
Section: Seprafilm Adhesion Barriermentioning
confidence: 99%
“…To investigate whether external support would reduce intimal hyperplasia at the site of venous graft anastamosis, rabbits undergoing bypass grafting of the right jugular vein to the right common carotid artery was performed in the presence or absence of wrapping the anastamosis with Seprafilm [67]. Evaluation at 1 month demonstrated that use of Seprafilm reduced both neointimal and medial thickening.…”
Section: Seprafilm Adhesion Barriermentioning
confidence: 99%
“…Bahcivan et al studied the effect of hyaluronic acidcarboxymethyl cellulose on neointimal hyperplasia experimentally. They claimed that HA prevents the development of neointimal hyperplasia on vein grafts through a positive effect on tissue repair due to its barrier-forming nature [18]. Thus, we studied the effects of a HA-based endothelial protection solution for vein grafts for the creation of AV fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Adventitial administration of gene transfer vectors and nanoparticles have also been studied to deliver platelet-derived endothelial cell growth factor (PD-ECGF) thymidine phosphorylase (TP) [39] and microRNA-145 (miR-145)loaded poly(lactic-co-glycolic acid) (PLGA) [40] to modulate SMC chemotaxis and phenotype from proliferative to contractile states. Fibrin sealants such as cyanoacrylate [41,42] , anti-adhesive agents such as hyaluronic acid-carboxymethyl cellulose (HA/CMC) [43] , and collagen cross-linking with photoactive tissue passivation [44] have also been investigated as methods of providing mechanical offloading to vein grafts without sheath implants. As with external vein graft stents, the long-term effects of these adventitial treatments remain to be seen and will remain a subject of future investigation.…”
Section: Modern Therapies To Prevent Vein Graft Failurementioning
confidence: 99%